(untitled) (International Journal of Environmental Sciences, 2025)
Amelogenesis imperfecta (AI) is a hereditary enamel disease that is typified by aberrant enamel development, manifesting in several clinical phenotypes, including hypoplastic, hypomaturation, and hypocalcified variations. The mutations impacting enamel matrix proteins and related structural elements constitute the genetic etiology of AI. Despite lots of research, the expression profiles of the main genes linked to enamel development AMELX, AMBN, ENAM and LAMB3 in patients with AI are still unclear. This study evaluates the differential expression of AMELX, AMBN, ENAM, and LAMB3 genes in dental tissue from subjects with AI compared to controls without AI. The experiment was performed using qPCR with the SYBR Green protocol and run in triplicate, including negative controls. Fold changes derived from ΔΔCt were reported as median values. Analysis was done on enamel-matrix expression of genes levels in amelogenesis imperfecta patients and non-AI controls in this study. AMELX expression was also significantly impaired in AI (median = 0.658) versus controls (median = 1.17; p = 0.0002). AMBN levels were also significantly lower in these patients (median = 0.287 vs. control median = 1.16; p = 0.001), and there was a significant decrease in ENAM expression (median = 0.223 vs. control median = 1.1; p = 0.007). Conversely, no significant change in LAMB3 mRNA was observed (patient median = 0.944 vs. control median = 1.17; p = 0.24). These findings conclude that the crucial enamel maturation genes for enamel formation, AMELX, AMBN, and ENAM, are specifically diminished in AI, whereas LAMB3 seems to not be disturbed in these defects. The results revealed qPCR-induced dysregulation in AI’s symptomatic enamel defects, highlighting the molecular mediators of biomineralization-related diseases.